Iron-Containing Protein-Mimic Supramolecular Iron Delivery Systems for Ferroptosis Tumor Therapy - Liu, Shuwei; Zhang, Mengsi; Jin, Hao; Wang, Ze; Liu, Yi; Zhang, Songling; Zhang, Hao (Journal of the American Chemical Society, 2023)
Ferroptosis provides an innovative theoretical basis and method for tumor therapy but is limited by the low efficiency of conventional iron delivery systems. Herein, an efficient supramolecular iron delivery system (SIDS) is demonstrated upon the hydrolysis of FeCl , condensation of amino acids, and self-assembly of iron-containing components. The as-assembled SIDS possesses a shuttle-like core/shell structure with β-FeOOH as the core and Fe /polyamino acid coordinated networks as shells. The iron content of SIDS is up to 42 wt %, which is greatly higher than that of ferritin. The iron-containing protein-mimic structure and shuttle-like morphology of SIDS facilitate tumor accumulation and cell internalization. Once exposed to the tumor microenvironment with overexpressed glutathione (GSH), the SIDS will disassemble, accompanied by the depletion of GSH and the release of Fe , leading to dual amplified ferroptosis. Primary studies indicate that SIDS exhibits outstanding antitumor efficacy on bladder cancer.